2015
DOI: 10.1364/boe.6.000690
|View full text |Cite
|
Sign up to set email alerts
|

Atypical prefrontal cortical responses to joint/non-joint attention in children with autism spectrum disorder (ASD): A functional near-infrared spectroscopy study

Abstract: Autism spectrum disorder (ASD) is a neuro-developmental disorder, characterized by impairments in one's capacity for joint attention. In this study, functional near-infrared spectroscopy (fNIRS) was applied to study the differences in activation and functional connectivity in the prefrontal cortex between children with autism spectrum disorder (ASD) and typically developing (TD) children. 21 ASD and 20 TD children were recruited to perform joint and non-joint attention tasks. Compared with TD children, childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…The statistical hypothesis test was performed on the difference of the two groups, showing the differences in HbO 2 for 5 channel pairs were significant, i.e., p<0.05 after the false discovery rate (FDR) correction. These 5 channel pairs were (3,17), (11,24), (10,20), (8,22) and (9,21), with the corrected p value being 0.0069, 0.0111, 0.0117, 0.0137, and 0.0431, respectively. To investigate atypical features of the spontaneous fluctuations for ASD, the fluctuation power for HbO 2 and Hb were also calculated and compared for each group and shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The statistical hypothesis test was performed on the difference of the two groups, showing the differences in HbO 2 for 5 channel pairs were significant, i.e., p<0.05 after the false discovery rate (FDR) correction. These 5 channel pairs were (3,17), (11,24), (10,20), (8,22) and (9,21), with the corrected p value being 0.0069, 0.0111, 0.0117, 0.0137, and 0.0431, respectively. To investigate atypical features of the spontaneous fluctuations for ASD, the fluctuation power for HbO 2 and Hb were also calculated and compared for each group and shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies with various imaging modalities have already revealed significant functional or structural alterations associated with ASD in brain regions [4][5][6][7][8][9][10][11]32]. However, there is a vigorous debate on the clinical use of diagnostic imaging for ASD [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies using optical methods to measure the hemodynamics of autism have used functional near‐infrared spectroscopy ( f NIRS), which can detect changes in hemoglobin concentration within the human brain based upon absorption coefficient calculations . More recently, the use of diffuse optical tomography (DOT) in autism spectrum disorder (ASD) was also demonstrated .…”
Section: Introductionmentioning
confidence: 99%
“…fNIRS has excellent time resolution and acceptable spatial resolution [4]. Due to its non-invasiveness, low cost and portability [5], fNIRS has been increasingly applied to various areas, such as the detection of deception.…”
Section: Introductionmentioning
confidence: 99%